ANALISIS EFEKTIVITAS DAN PERTUMBUHAN PENDAPATAN, BELANJA DALAM PENGELOLAAN KEUANGAN DESA HUTA PADANG, KECAMATAN BANDAR PASIR MANDOGE - Riska Tamalia Setia Naiborhu; Calen Calen; Henry Dunan Pardede (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This research aims to determine and analyze the effectiveness and growth of income and expenditure in financial management in Huta Padang Village, Bandar Pasir Mandoge. The type of research used in this research is descriptive qualitative. The data used in this research is secondary data in the form of the 2021-2023 Village Revenue and Expenditure Budget (APBDes) report obtained from the Office of the Head of Huta Padang Village, Bandar Pasir Mandoge District. The analysis technique used in this research uses the effectiveness ratio and growth ratio formulas.